Appendix: Heterogeneous Effects of Women’s Schooling on Fertility, Literacy and Work: Evidence from Burundi’s Free Primary Education Policy - Wild, Frederik; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2023)
Associated main article: 20230509_EduFer_article.pdf
Keywords: Child care; Children; Fertility; Income distribution; Sub-Saharan Africa; Youth; Education; Family planning; Migration; Economic development; Female Education; Human Development; Education Policy; Educational Influence; Child Development; Human Resources